Free and fair elections: Mugabe and the challenges facing elections in Zimbabwe. (2015) - Hove, Mediel; Harris, Geoff
This article evaluates Zimbabwe's election processes which many observers believe failed the test of being 'free and fair', guided by the mandate of the Government of National Unity as enshrined in the Global Political Agreement. In fact, it reveals the extent to which President Mugabe and his party were able to undermine the electoral process in Zimbabwe by violating principles of democracy. It argues that the Government of National Unity was unable to institute reforms in the media and the Zimbabwe Electoral Commission after the 2008 deeply contested elections because of President Mugabe's tactics of subverting democratic electoral processes. Furthermore, it asserts that the media and the Zimbabwe Electoral Commission acted in ways which strongly advantaged the Zimbabwe African National Union Patriotic Front to the detriment of the opposition political parties including the Movement for Democratic Change formations. It concludes that several pre-requisites must be met by a number of institutions and other crucial stakeholders for future peaceful, free and fair, credible and legitimate elections to be held in Zimbabwe.